Reconstruction of the ethos of industrial civil engineer career in Chile: a preliminary approach - Pasmanik Volochinsky, Diana; Rodríguez Araneda, María José; Reyes Espejo, María Isabel; Tarride Fernández, Mario (Acta Bioethica, 2016)
Looking for Industrial Engineering professional ethos reconstruction from its actors’ subjectivity, a qualitative research on professional experience and meaning construction on ethics and interculturality, in Chilean Industrial engineers and students who had already finished their last practicum, is reported. All participants had studied or were still studying in Chilean public universities. Inquiry was performed by means of individual and group interviews which provided 19 texts, afterwards analyzed by means of Grounded Theory procedures. Results allow to adventure that Industrial Engineering ethos, in Chile, had as its nucleus efficiency, and so, tasks quality itself. Nevertheless, this ethos is tensioned with the aspiration to transform this discipline in one whose professionals also would work being conscious of its social responsibility. According to these results, it’s feasible to presume that, at least in Chile, Industrial Engineering is experiencing a reconstruction process in its moral character.